Contribution of Gambo Music to the Development of Islam in Sanggar Subdistrict, Bima Regency - Vivifebselasari, Vivifebselasari; Nurhidayat, Nurhidayat; Hamiruddin, Hamiruddin (Jurnal Mercusuar, 2021)
This writing discusses about "Dakwah through Music" (Case Study of Gambo Music in Sanggar Sub-district, Bima Regency). This study aims to determine: 1) How is the form of gambo music performance in Sanggar Sub-district, Bima Regency? 2) How do people view gambo music in Sanggar Sub-district, Bima Regency? 3) What is the contribution of gambo music to the development of Islam in Sanggar Sub-district, Bima Regency? This writing aims to examine the values of dakwah in gambo music lyrics. Gambo Music is a musical instrument that has long been played by the community in Sanggar Sub-district. In addition to playing gambo music in certain traditional ceremonies, gambo music is also commonly played at other times according to the taste and pleasure of the players. Therefore, gambo music is considered necessary to be developed as an attractive media for dakwah in Sanggar Sub-district. This study uses a qualitative research method with an ethnographic approach. The subjects of this study are gambo music players in Sanggar Sub-district.